A study of nano structure by roll to roll imprint lithography - Hassan, Suhaimi (2015)
Imprint lithography process is a unique printing technique that create graphic, electronic and biomedical printed on substrates. PET plastics are an example of materials that can be used as printing substrate in producing nano-scale electronic and medical devices. Here, it is proposed that extending imprint lithography technique into the multiple nano-structure printing fine solid lines onto substrate. Imprint lithography is a low cost printing technique commonly used in manufacturing and printing industry. This study exhibit successful fine solid lines imprinting below 1 micrometer in line width, gap and height on polyethylene-terephthalate (PET) substrate. This paper illustrates the use of imprint lithography method in producing multiple nano-solid lines printing capability as application of printing electronic, graphic and bio-medical.